2022
DOI: 10.1002/advs.202205303
|View full text |Cite
|
Sign up to set email alerts
|

3D MXene‐Based Flexible Network for High‐Performance Pressure Sensor with a Wide Temperature Range

Abstract: With the increasing popularity of smart wearable devices, flexible pressure sensors are highly desired in various complex application scenarios. A great challenge for existing flexible pressure sensors is to maintain high sensitivity over a wide temperature range, which is critical for their applications in harsh environments. Herein, a flexible piezoresistive sensor made of polyetherimide (PEI) fibrous network evenly covered with MXene nanosheets is reported to construct conductive pathways, showing ultrahigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 44 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The results show that LPV-5 presents stable responses with excellent repeatability. Figure d shows a high sensitivity response over a wide response range compared to reported pressure sensors, demonstrating the supereminent sensing properties of our LPV-5 sensor. …”
Section: Resultsmentioning
confidence: 68%
“…The results show that LPV-5 presents stable responses with excellent repeatability. Figure d shows a high sensitivity response over a wide response range compared to reported pressure sensors, demonstrating the supereminent sensing properties of our LPV-5 sensor. …”
Section: Resultsmentioning
confidence: 68%
“…Figure and Table S1 show the sensing performance comparison between the fabricated flexible pressure sensor and other high-performance piezoresistive sensors reported in the literature. ,,, It is found that most pressure sensors cannot achieve high sensitivity and wide linear range simultaneously through material selection and structural design, exhibiting a trade-off between these two properties. In this work, the PI@Ag sensors possess both high sensitivity (197 kPa –1 ) in a medium-pressure region (10–20 kPa) as well as relatively high sensitivity (13.73 kPa –1 and 47.6 kPa –1 ) in the low- (100 Pa–10 kPa) and high-pressure regions (20–50 kPa).…”
Section: Resultsmentioning
confidence: 99%
“…Flexible pressure sensors, which exhibit excellent real-time sensing, portability, and high integration, have showing promising applications in human motion detection, electronic skin, human–computer interaction, etc. Depending on the sensing mechanism, flexible pressure sensors could be broadly divided into four types: piezoelectric, , piezoresistive, capacitive, and triboelectric. , Among them, piezoresistive sensors show various advantages of simple fabrication, low cost, easy signal acquisition, and high sensitivity. Although piezoresistive sensors have made great strides, it is still a great challenge to achieve both high sensitivity and benign stability simultaneously for subtle or enormous human body movement (e.g., pulse, joint flexion, etc.…”
Section: Introductionmentioning
confidence: 99%